Assessment of ground water quality around Mathuradaspura dumpsite, Jaipur, Rajasthan. (27th April 2021) - Sharma, Smita; Mathur, N.D.
The increased mismanagement of municipal waste has led to the deterioration of the environment in various areas. The present study attempts to assess the ground water quality around open dumpsite at Mathuradaspura, Jaipur. Twenty-five grab samples were collected around this dumpsite. The pH levels were found to be in the range of 6.3 to 7.7, EC was found to be between 65-287 μS/cm, nitrate 85 mg/l, total dissolved solids 1, 400-1, 670 mg/l, carbonate 546-663 mg/l, chemical oxygen demand 8.09-8.70 mg/l, chloride 668.76-696 mg/l, biological oxygen demand 1.1-1.6 mg/l, alkalinity was 703-714 mg/l and sulphate 84-95 mg/l. Fluoride was found to be in the range of 1.35-1.48 mg/l and dissolved oxygen from 2.2-2.4 mg/l. There was found a high negative correlation between pH and fluoride and EC and chloride and EC and dissolved oxygen. There was a high positive correlation between fluoride and COD, alkalinity and TDS. The results suggest that the water quality in the area surrounding the dumpsite has deteriorated and is not fit for drinking purposes.